DAMPAK EKONOMI TERHADAP MORATORIUM PENGIRIMAN TKI KE TIMUR TENGAH ERA JOKOWI - Laksono, Dwi; Hakim, Lukmanul (Dauliyah Journal of Islamic and International Affairs, 2022)
The world oil boom in the 1970s and its peak in the 1980s made Middle Eastern countries rich in petrodollars. The impact is job seekers around the world to try their luck there. Many job seekers become labor (laborers), both in the formal and informal sectors, including Indonesian Migrant Workers (TKI). But unfortunately, almost all of these migrant workers work in the informal sector by working as domestic workers, especially women, manual workers, or as drivers for male migrant workers Humans in the jahiliyah period, especially in Arabia, were divided into many strata, which from one level to the next, had a form of power. Slaves, being the lowest strata, even their human values are not fully recognized, because they are considered human beings who are not free. So the owner, can do anything to themselves, without being limited by norms and ethics. Jokowi's desire for a memoratorium for TKI workers is very strong stems from the many cases of abuse experienced by several workers who come from Indonesia. Then whether Jokowi's policy of wanting a TKI memoratorium has a good impact or is it the opposite, seeing from another perspective, TKI are also heroes of state foreign exchange.